"Not My Father's Son": Qualitative Investigation of U.S. Men's Perceptions of Their Fathers' Expectations and Influence. Issue 2 (June 2018) - Levant, Ronald F.; Gerdes, Zachary T.; Jadaszewski, Stefan; Alto, Kathleen M.
The present study examined men's perceptions of their father's general expectations of them when they were growing up and what the effects have been on their lives. Previous research suggests fathers influence sons' development, but few studies have examined sons' perceptions qualitatively. Participants were 252 demographically diverse community-dwelling and college men (ages 18-78; 36.5% men of color). Descriptive coding and content analysis were used to analyze written open-ended responses from an online questionnaire. Results suggest that fathers' expectations for their sons are quite influential. Common topics of expectations reported by participants included Academics, Work Ethic, Athletics, Family, Career, Independence and Self-Reliance, Authenticity, and Happiness. Sons who perceived their fathers as supporting their authentic selves without having unattainable expectations reported positive impacts. Rigid and ill-fitting expectations may have negative effects. These findings suggest fathers are an important influence on their sons with positive or negative impacts on their well-being, depending on how well the expectations fit their sons.